L’architettura paranoica di Kafka - Sferrazza Papa, Ernesto C. (Mechane, 2023)
In this short essay, I analyse the function of constructions in Kafka’s work. The proposed interpretative hypothesis is that they represent the materialization of the protagonists’ anguished states. In conclusion, I propose a parallel between Kafka’s work and Coetzee’s novel Waiting for the Barbarians.